SUSTAINABLE DEVELOPMENT GOAL 4: PENCAPAIAN PENDIDIKAN BERKUALITAS PADA 34 PROVINSI DI INDONESIA TAHUN 2021 - Alma Safitri, (2023)
Quality education is one of the things that the Sustainable Development Goals (SDGs) want to achieve, which is goal 4: Quality Education. In the condition of education, there are differences in the reporting of the quality of education in the 34 provinces. In order to evaluate optimally and find out the goals of quality education in 34 provinces in Indonesia, the Qualitative Comparative Analysis (QCA) used in this case to determine the distribution and grouping of provinces in Indonesia based on the condition of the quality of education. The population in this study is the condition of education in 34 provinces in Indonesia and the sample in this study is the condition of education in the population aged 15 years and over in 2021. The results showed that there were 2 (two) clusters with educational conditions that were not optimal and and 3 (three) clusters with optimal educational conditions. It was found that the optimal areas were dominated by provinces in Java, Kalimantan, Sumatra, Sulawesi and Maluku. This implies that the education program implemented by the local regional government has been effective in creating quality education, this can be used as an example for other provinces in overcoming educational problems in their regions.